Dentre plantas e mulheres: a porta de entrada do universo místico e poético que envolve mulheres em Salvaterra - PEIXOTO, Lanna Beatriz Lima (Universidade Federal do Pará, 2020)
In this present study we show preliminary reflections about the mythical universe involving women and female space in the Marajó region. We present data from the first two trips to the countryside, where we highlight two women in particular: Mrs.Marta in Joanes district, and Mrs. Joana, in a "quilombo", both located in the municipality of Salvaterra. Here, we expose some notes raised by the encounter with these two women, to think about their experiences from the dialogue with a specific bibliography. At first the existence of a common theme helped us we enter the universe of their daily lives and more directly from their yards, from where the knowledge related to medicinal plants have emerged as the tip of a ball, comprising memories and knowledge in around healing practices of shamanism and local mysticism, involving mainly the female figure we intend to address this during the discussion in this article.